2023
DOI: 10.1002/gps.5942
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors for postoperative delirium following major abdominal surgery: A systematic review and meta‐analysis

Abstract: Objectives Postoperative delirium (POD) is a common postsurgical complication. The early identification of its risk factors is the first step toward reducing POD. The predictive factors for POD in patients after major abdominal surgery remain obscure. Therefore, this meta‐analysis aimed to comprehensively summarize the risk factors of POD after major abdominal surgery. Methods POD studies published between January, 1900 and June 2022 were obtained by searching PubMed, Cochrane Library, Web of Science, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(139 reference statements)
0
0
0
Order By: Relevance
“…POD and POCD have different pathogenesis, although they share similar risk factors [ 8 ]. Previous studies have demonstrated that long-term exposure to anesthesia could cause neurotoxicity, leading to POCD and POD [ 9 , 10 ]. In recent years, intraoperative brain function monitoring has become increasingly common in various surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…POD and POCD have different pathogenesis, although they share similar risk factors [ 8 ]. Previous studies have demonstrated that long-term exposure to anesthesia could cause neurotoxicity, leading to POCD and POD [ 9 , 10 ]. In recent years, intraoperative brain function monitoring has become increasingly common in various surgical procedures.…”
Section: Introductionmentioning
confidence: 99%